El enriquecimiento injustificado como mecanismo de tutela frente de los derechos de la personalidad - Geldres Campos, Ricardo (2023)
Through this article, the author develops the figure of illicit enrichment, where it arose, how it is treated in doctrine and why its use is limited in the national environment; in this regard, he postulates a typological construction of the types of enrichment within the framework of the Peruvian Civil Code focused on the existing differences in restitutive problems, placing special emphasis on the protection of personality rights.